1985
DOI: 10.1080/00332747.1985.11024287
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Behavior and Therapeutic Progress: Therapists and Clients Rate Themselves and Each Other

Abstract: To measure the extent to which progress in psychotherapy can be predicted from the interpersonal styles of therapists and clients, 42 outpatients and their 11 therapists rated themselves and each other on Benjamin's Structural Analysis of Social Behavior (SASB) scales. In addition, therapists rated amount of client change and therapy success-failure, based on the outcome section of the Rogers and Dymond (1954) scale, and clients used the Strupp, Fox, and Lessler (1969) questionnaire to evaluate progress-to-dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Research suggests that SASB-rated complementary control-submission interaction is associated with less change in therapy. 43 Such a maintaining role could apply also to positive interpersonal variables like self-protection. Self-protection relates to trusting and relying on others (positive submission), while not taking the initiative oneself.…”
Section: Implications For Patient-therapist Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that SASB-rated complementary control-submission interaction is associated with less change in therapy. 43 Such a maintaining role could apply also to positive interpersonal variables like self-protection. Self-protection relates to trusting and relying on others (positive submission), while not taking the initiative oneself.…”
Section: Implications For Patient-therapist Interactionmentioning
confidence: 99%
“…Also, helping/protecting patient behavior toward therapists, theoretically corresponding to self-protection, has been shown to strongly relate to less improvement. 43 Thus, patients high in self-protection may engage in more protecting behaviors toward the therapist also, resulting in less change. In summary, dominance-submission interactions neutral or even positive in valence may relate to poorer outcome, which would be interesting to test directly in future research.…”
Section: Implications For Patient-therapist Interactionmentioning
confidence: 99%
“…Henry et al (1986) and Svartberg and Stiles (1992) found that corresponding with friendly complementarity along the affiliation dimension was associated with positive therapeutic processes and outcomes, while noncomplementary communications disrupted positive process and outcome. Rudy, McLemore, and Gorsuch (1985) found that complementarity on the affiliation dimension was associated with therapist and client rating therapy as successful, however affiliation complementarity was not a strong predictor of other outcomes including symptom reduction and therapist ratings of the client change. Weinstock-Savoy (1986) found that affiliation complementarity was associated with outcomes as rated by observers, therapists, and clients.…”
Section: Affiliation Complementaritymentioning
confidence: 93%
“…While finding factors that compellingly predict therapeutic outcome is difficult and often disappointing (Norcross, 2002), interpersonal process consistently plays an integral role in the course of therapeutic change (Benjamin & Critchfield, 2010). In some studies, as much as 65% of the variance in therapeutic progress has been attributed to interpersonal process and reflexive social behavior (Rudy, McLemore & Gorsuch, 1985) indicating that it is not only a consistent predictor of therapeutic outcome, but also one that is robust. Both empirical research and theory indicate that social behavior and interactions play an important role in the process of psychotherapeutic change.…”
Section: Chapter 1: Theoretical Basismentioning
confidence: 99%
“…In some studies, as much as 65% of the variance in therapeutic progress has been attributed to interpersonal process and reflexive social behavior (Rudy, McLemore & Gorsuch, 1985) indicating that it is not only a consistent predictor of therapeutic outcome, but also one that is robust. Both empirical research and theory indicate that social behavior and interactions play an important role in the process of psychotherapeutic change.…”
Section: Chapter 1: Theoretical Basismentioning
confidence: 99%